2017
DOI: 10.1007/s10928-017-9564-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of dexmedetomidine during analgosedation in ICU patients

Abstract: Dexmedetomidine (DEX) is a fairly new alfa2-agonist which has been increasingly used in recent years for analgosedation, mostly because it offers a unique ability of providing both moderate level of sedation and analgesia without respiratory depression. Despite of many papers published, there are still only a few concerning the PK of the drug given as long-term infusion in ICU patients. The aim of this work was to characterize the population pharmacokinetics of dexmedetomidine and to investigate the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
3
7
0
2
Order By: Relevance
“…In the present study, a 2‐compartment model best described the data, which was consistent with other published studies on dexmedetomidine PK 3,9,34‐37 . The typical value of systemic clearance equaled 34.7 L/h, which was in the lower range of literature values (33.7–53.4 L/h) 3,9‐11,32,34‐36,38,39 This value was also slightly lower than values estimated for other ICU patients with continuous infusion lasting >24 hours (38.5, 39.7, 43, and 57 L/h) 10,35,37,38 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, a 2‐compartment model best described the data, which was consistent with other published studies on dexmedetomidine PK 3,9,34‐37 . The typical value of systemic clearance equaled 34.7 L/h, which was in the lower range of literature values (33.7–53.4 L/h) 3,9‐11,32,34‐36,38,39 This value was also slightly lower than values estimated for other ICU patients with continuous infusion lasting >24 hours (38.5, 39.7, 43, and 57 L/h) 10,35,37,38 .…”
Section: Discussionsupporting
confidence: 90%
“…The intercompartmental clearance equaled 40.8 L/h and was similar to literature values for ICU patients (39.7, 46.4 L/h) 38,35 . The volume of distribution at steady state (108.6 L) was consistent with the summary of product characteristics of Dexdor (90–151 L) and with values estimated in other studies (93‐132 L) 6,10,35,37 . Some differences in typical model parameters are inevitable and may result from the patient's clinical condition and between‐study differences in experimental designs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is metabolised by glucuronidation and CYP2A6 hydroxylation and subsequently excreted in urine almost exclusively as metabolite [2]. Its pharmacokinetics has been described by a two-compartmental model both in adults [3][4][5][6][7] and children [8][9][10][11][12]. Still, other investigators have also reported the disposition of dexmedetomidine according to one-compartment [13] and three-compartment [14][15][16] models.…”
Section: Introductionmentioning
confidence: 99%
“…Враховуючи той факт, що зміни активності головного мозку тісно пов'язані з його метаболізмом, що без постійного інтенсивного надходження АТФ сповільнюється клітинний синтез, пригнічуються функції нейронів і, що для забезпечення енергетичних потреб головного мозку процес тканинного дихання, що потребує кисень, є більш ефективним, ніж гліколіз [13]. Важливим є своєчасне призначення патогенетично обґрунтованих речовин у складі інтенсивної терапії (ІТ), які б з першої хвилин впливали на провідний механізм втрати свідомості.…”
Section: вступunclassified